Practical Trends in Anesthesia and Intensive Care 2017 (Springer International Publishing, 2018)
The book is a useful guide to the management of the most-debated hot topics of practical interest in anesthesia and intensive care. It reviews the state of the art of issues related to both intensive care medicine and anesthesia, such as assisted ventilation, ultrasound assessment of renal function, sedation during non-invasive ventilation, subarachnoid hemorrhage, coagulation disorders in septic shock, difficult airways management and hemodynamic monitoring during anesthesia. Written by leading experts and including updated references, it provides a comprehensive, easy-to-understand update on anesthesia and intensive care. The book clearly explains complex topics offering practicing clinicians insights into the latest recommendations and evidence in the field while, at the same time, making it a valuable resource for students new to the study of anesthesia and intensive care.